The role of chest ultrasonography in the management of respiratory diseases: document II - Smargiassi, Andrea; Inchingolo, Riccardo; Soldati, Gino; Copetti, Roberto; Marchetti, Giampietro; Zanforlin, Alessandro; Giannuzzi, Rosangela; Testa, Americo; Nardini, Stefano; Valente, Salvatore (Multidisciplinary respiratory medicine, 2013)
Chest ultrasonography can be a useful diagnostic tool for respiratory physicians. It can be used to complete and widen the general objective examination also in emergency situations, at the patient’s bedside. The aim of this document is to promote better knowledge and more widespread use of thoracic ultrasound among respiratory physicians in Italy. This document II is focused on advanced approaches to chest ultrasonography especially in diagnosing sonographic interstitial syndrome with physical hypotheses about the genesis of vertical artifacts, differential diagnosis of cardiogenic pulmonary edema and non-cardiogenic pulmonary edema, raising diagnostic suspicion of pulmonary embolism, ultrasound characterization of lung consolidations and the use of ultrasonography to guide procedural interventions in pulmonology. Finally, document II focuses on chest ultrasonography as useful diagnostic tool in neonatal and pediatric care.